Systemic inflammatory response of COVID-19 and its morphological expression, multiple organ damage - José Domingo Hurtado de Mendoza Amat; Teresita Montero González; Israel Borrajero Martínez; Virginia Capó de Paz; Laura López Marín; Carlos Domínguez Álvarez (Revista Cubana de Medicina Militar)
Systemic inflammatory response of COVID-19 and its morphological expression, multiple organ damage